Speech Acts In Classroom Discourse at SMP N 12 Palu - Alya; Asrianti; Arum Pujining Tyas (Universitas Muria Kudus, 2026)
This study aims to describe the form and function of speech acts in classroom discourse at State Junior High School 12 Palu. This study uses a qualitative approach. The data consists of oral utterances collected through recording techniques, free conversation listening techniques, and note-taking techniques in classes IX A and IX B. Data analysis was conducted using the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing/verification. The results of the study show that there are three forms of assertive speech acts, namely stating, informing, and explaining; one form of commissive speech act, namely promising; six forms of directive speech acts, namely requesting, advising, prohibiting, commanding, asking, and giving permission; and five forms of expressive speech acts, namely apologizing, thanking, praising, complaining, and sarcasm, and declarative speech acts were found in three forms, namely deciding, canceling, and punishing. Twenty-two functions were then found, such as stating, informing, explaining, promising, requesting, advising, prohibiting, preventing, commanding, ordering, requiring, asking, agreeing, allowing, apologizing, thanking, praising, complaining, Insinuating, deciding, canceling, and punishing. This research has significant implications for improving communication methods in learning. By understanding and applying a variety of speech acts in a balanced manner, classroom interactions are no longer one-way but rather become dialogic and participatory.